Advances in two-dimensional materials for energy-efficient and molecular precise membranes for biohydrogen production. (November 2022) - Loh, Ching Yoong; Ye, Wenyuan; Fang, Shengqiong; Lin, Jiuyang; Gu, Ailiang; Zhang, Xinyu; Burrows, Andrew D.; Xie, Ming
Graphical abstract: Highlights: Downstream waste-to-hydrogen process can be realised with 2D material-based membrane. Mechanism and fabrication methods of 2D material-based gas separation membrane are outlined. 2D COFs, MOFs and carbon-based materials are reviewed for H2 /CO2 gas separation membranes. Challenges and future prospect of 2D material-based membrane in waste-to-hydrogen are discussed. Abstract: Waste management has become an ever-increasing global issue due to population growth and rapid globalisation. For similar reasons, the greenhouse effect caused by fossil fuel combustion, is leading to chronic climate change issues. A novel approach, the waste-to-hydrogen process, is introduced to address the concern of waste generation and climate change with an additional merit of production of a renewable, higher energy density than fossil fuels and sustainable transportation fuel, hydrogen (H2 ) gas. In the downstream H2 purifying process, membrane separation is one of the appealing options for the waste-to-hydrogen process given its low energy consumption and low operational cost. However, commercial polymeric membranes have hindered membrane separation process due to their low separation performance. By introducing novel two-dimensional materials as substitutes, the limitation of purifying using conventional membranes can potentially be solved. Herein, this article provides a comprehensive review of two-dimensional materials as alternatives to membrane technology for the gas separation of H2 in waste-to-hydrogen downstream process. Moreover, this review article elaborates and provides some perspectives on the challenges and future potential of the waste-to-hydrogen process and the use of two-dimensional materials in membrane technology.